Against All Odds - Soni, Shriprakash; Saxena, Rohini Sawalkar (International Research Journal of Management, IT & Social Sciences, 2017)
A successful woman entrepreneur, Ms. Vrinda Navare has established âVrindaâs Bakes & Fast Foodâ in 1993 initially with manufacturing of bakery products only. Later on in the year 1996 fast food items were added in product basket as a need of hour. At present, firmâs turnover is Rs. 90 lakhs with 15 full-time and 30 part-time workers...